2002
DOI: 10.1634/theoncologist.7-suppl_5-3
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Role of Topotecan in the Treatment of Recurrent Ovarian Cancer

Abstract: Ovarian cancer is the fifth leading cause of cancer death in women. Most patients with ovarian cancer respond to first-line chemotherapy, but many relapse within 18 to 22 months. The development of efficacious salvage therapies that increase overall survival while maintaining quality of life is a great challenge in the treatment of this disease. Topotecan, a novel topoisomerase I inhibitor, is currently indicated for the treatment of recurrent metastatic carcinoma of the ovary. In patients with relapsed ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 28 publications
(19 reference statements)
6
19
0
Order By: Relevance
“…These findings are consistent with data from other tumour types such as ovary and testis, which demonstrate a difference in outcome regarding patients with refractory and relapsed disease (Thigpen et al, 1993;McCaffrey et al, 1997;Herzog, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with data from other tumour types such as ovary and testis, which demonstrate a difference in outcome regarding patients with refractory and relapsed disease (Thigpen et al, 1993;McCaffrey et al, 1997;Herzog, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the findings of Goldwasser et al, fewer patients required blood cell transfusions or growth factor support to manage the hematologic toxicity of topotecan during later courses of therapy. Although no absolute remission data could be generated from that study, all of the patients achieved a complete or partial remission or stable disease during the course of topotecan treatment [64]. That study supports the safe and long-term use of topotecan as palliative therapy for the advanced ovarian cancer patient.…”
Section: Topotecanmentioning
confidence: 70%
“…An ORR (both cohorts) of 12% was observed, including partial responses (PRs) in 2 of 22 patients initially progressing on topotecan and 3 of 35 patients initially progressing on paclitaxel when they received their third-line therapy [27]. The results of these studies suggest that prior treatment with topotecan or paclitaxel may not adversely affect future responses to the crossover treatment [12]. Additionally, albeit limited by patient numbers, these findings suggest that patients could benefit from receiving topotecan in a front-line strategy because topotecan had activity against tumors that were resistant to both platinum and paclitaxel.…”
Section: Antitumor Activity Of Topotecan and Potential For Non-crossrmentioning
confidence: 86%
“…The U.S. Food and Drug Administration approved the agent in 1996 for the treatment of metastatic carcinoma of the ovary after failure of first-or second-line chemotherapy. Several studies have demonstrated the efficacy of topotecan as a second-line therapy, with tumor response rates ranging from 13%-33% [6][7][8][9][10][11], (review by Herzog pp 3-10 [12]). The maximum tolerated dose (MTD) of topotecan was 1.5 mg/m 2 /day using a 5-day regimen every 21 days.…”
Section: Introductionmentioning
confidence: 99%